The Empowerment of Tourism Community Through Corporate Social Responsibility (CSR) Program - Djoko Putro Utomo; Ravik Karsidi; Ismi Dwi Nurhaeni; Drajat Tri Kartono (Indonesian Association for Public Administration (IAPA), 2021)
Community empowerment has an important role in building sustainable tourism. One of the plans used for community empowerment in tourism areas is the implementation of Corporate Social Responsibility (CSR) which involves the implementation and participation of the community in program activities. This study aims to define and describe community empowerment in tourism areas through the implementation of Corporate Social Responsibility (CSR). The research method used is descriptive qualitative with a single embedded case study. The results of this study are: (1) CSR profile of Bank Jatim (East Java Bank), (2) tourism community empowerment based on the CSR program, (3) the implementation of CSR program in tourism area of Pancer Door Beach, and (4) the results of the tourism community empowerment in Pancer Door Beach from CSR program.